Understanding Different Perspectives on Salvation - Chrispine Katiyi Banda (Eastern African Journal of Humanities and Social Sciences)
Salvation is one of the widely bounded themes in the scripture that has gained traction under discourse due to the many perspectives under which it is viewed. This paper presents a discussion on the various perspectives of salvation both from a historical viewpoint and within the current theologies. The aim is to provide an understanding of salvation from different perspectives as observed by Augustine, Roman Catholic, Liberation, Secular, Evangelical and Biblical theologies. The study will promote reflection and debates among the scholars which will enhance problem-solving. The objective was therefore achieved through a review of various literary studies with biblical references to the term salvation and interview proponents of different theologies. The study, however, finds that despite the wide range of how different theologies view salvation, the only way to salvation is properly stipulated in the bible, thus it supports the biblical theory that salvation is by grace through faith, and furthermore, salvation is wholly an act of God. While this study was limited to the analysis of the term through a review of past studies, this paper recommends further study based on contemporary society collecting primary data on how different people view salvation.